Development of Thematic Magnetic Board Media (PAMANTIK) in Thematic Learning in Third Grade Elementary Schools - Rahil Nurmeilana; Lukman Nulhakim; Suparno Suparno (Universitas Pendidikan Ganesha, 2020)
In general, the use of instructional media in elementary schools is still lacking. The development of learning media that is more varied and innovative and integrated into the 2013 curriculum is needed. One of them is the Thematic Magnetic Board (PAMANTIK) media developed by thematic learning and is integrated with the 2013 curriculum. The purpose of this study is to analyze the process of developing instructional media. PAMANTIK according to the characteristics of thematic learning and knowing the feasibility of PAMANTIK learning media. A team of media experts carried out the results of the feasibility of this development research, material experts, and education experts with the interpretation category